The drawbacks of preferential trade agreements in Asia - Heribert Dieter (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
Preferential trade agreements have spread throughout Asia. However, they have not facilitated intra-regional trade as much as their supporters have suggested. The complexities of rules of origin - part and parcel of all preferential agreements - have resulted in low utilization rates in Asia. The key driver of trade integration in Asia has instead been the rise of China. In the past two decades, China has managed to establish itself as the indispensable trading partner in the region. In 2011, China ran a trade deficit with its neighbouring countries whilst running surpluses with the USA and the EU. At the same time, deeper trade integration in Asia, e.g. an Asian wide customs union, appears to be an unrealistic goal. At this juncture, the political obstacles that hinder a deepening of co-operation are formidable. Other Asian countries wish to cooperate with China, but they demonstrate an ever-rising reluctance to enter far-reaching integration projects with Bejing.
Keywords: F14; F15; F55; 330; Regional integration; Asian co-operation; ASEAN; China; preferential trade agreements